Implantable loop recorders in patients with heart disease: comparison between patients with and without syncope - Jolien W Roos-Hesselink; Michelle Michels; Tamas Szili-torok; Judith M A Verhagen; Rohit E Bhagwandien; Sing-Chien Yap; DOMINIC THEUNS; Amira Assaf; Rafi Sakhi (Open Heart)
Objective Patients with heart disease are at increased risk for sudden cardiac death. Guidelines recommend an implantable loop recorder (ILR) for symptomatic patients when symptoms are sporadic and possibly arrhythmia-related. In clinical practice, an ILR is mainly used in patients with unexplained syncope. We aimed to compare the clinical value of an ILR in patients with heart disease and a history of syncope versus those with non-syncopal symptoms.Methods In this observational single-centre study, we included symptomatic patients with heart disease who received an ILR. The primary endpoint was an actionable event which was defined as an arrhythmic event leading to a change in clinical management. The secondary endpoint was an event leading to device implantation.Results One hundred and twenty patients (mean age 47±17 years, 49% men) were included. The underlying disease substrate was inherited cardiomyopathy (31%), congenital heart disease (28%), channelopathy (23%) and other (18%). Group A consisted of 43 patients with prior syncope and group B consisted of 77 patients with palpitations and/or near-syncope. The median follow-up duration was 19 months (IQR 8–36). The 3-year cumulative event rate was similar between groups with regard to the primary endpoint (38% vs 39% for group A and B, respectively, logrank p=0.54). There was also no difference in the 3-year cumulative rate of device implantation (21% vs 13% for group A and B, respectively, logrank p=0.65).Conclusion In symptomatic patients with heart disease, there is no difference in the yield of an ILR in patients presenting with or without syncope.